Effects of diesel oil spill on macrobenthic assemblages at the intertidal zone: A mesocosm experiment in situ. (December 2019) - Zhou, Zhengquan; Li, Xiaojing; Chen, Linlin; Li, Baoquan; Wang, Chuanyuan; Guo, Jie; Shi, Pu; Yang, Lufei; Liu, Bo; Song, Bo
Abstract: The oil spill accidents may drastically impact the environment and ecosystem at intertidal zones. The spilled oil will penetrate the sediments and accumulate to cause lethal or sublethal effects on the benthic invertebrates. An M-BACI experiment was manipulated in situ to assess the ecological responses of benthic macrofauna to different degrees of diesel oil spill. Both biotic and abiotic parameters were studied for 126 days, subjected to both "pulse" and "press" oil contaminations. The content of aliphatic hydrocarbons (displayed as ratios of n -C17/Pr and n -C18/Ph) slightly dropped then continuously existed in the sediment during the experiment time. The macrofaunal assemblage structures were dramatically altered in species number, abundance and biomass. In general, it takes longer time for the macrofauna assemblages to recover under high concentration oil spill than that under low concentration. Our results highlight the diversified strategies for survival and recolonization among dominant species, which distinguish themselves between: i ) tolerant species, ii ) opportunistic species, and iii ) equilibrium species. Highlights: The general ecological response of benthic macrofauna to the diesel oil spill were studied using a M-BACI design. Species composition was significantly changed by the simulated diesel oil spill. Community abundance and species number gradually recovered at low concentration oil polluted areas within 63 days. Tolerant species, opportunistic species and equilibrium species were categorized according to biological responses to the oil spill.